(untitled) (Journal of the College of Basic Education, 2022)
Flavonoid compounds were studied in some orders of the genus Ranunculus of the family Ranunculaceae growing in Iraq and used as evidence in the chemical classification of the orders of the genus, as flavonoids were investigated in 14 orders, and its results were revealed in terms of separation and diagnosis by high-efficiency liquid chromatographic analysis HPLC)) High Performance Liquid Chromatography .Six types of flavonoid compounds were detected based on the data generated by HPLC technology, and based on the variation in the presence or absence of these flavonoid compounds identified in the studied plant ranks, a cluster analysis was conducted for the flavonoid compounds’ products, and the plant ranks were divided according to groups that reflect the chemical relationship between them.